Evidence of human settlement during the Epipalaeolithic in the north east of El Eulma (Wilaya of Setif) - derbal, saliha; bahra, nadia; merzoug, Suhaila (The Algerian Historical Journal, 2026)
The north-eastern region of El Eulma is one of the North African areas that witnessed human settlement during the Epipalaeolithic, a period characterised by a marked improvement in the stone tool production. Given its archaeological importance, a descriptive-analytical approach was adopted to shed light on the evidence of human occupation in the region, describing each site and identifying its characteristics, then analysing the data by comparing it with other sites. The archaeological survey led to the discovery of 5 new escargotieres and the relocation of previously known ones. It also shows a preferential localisation of the sites on the plains and near the waterways of Oued Djermane. Furthermore, the archaeological material and the comparison with other sites in the region argue in favour of an attribution to the Upper Capsian or the Neolithic of Capsian tradition.